Analisis determinan tingkat konsumsi pangan di Provinsi Jawa Tengah - Radita Mauli Al Adha; Ismadiyanti Purwaning Astuti (Jurnal Paradigma Ekonomika, 2024)
Food consumption is a need for goods in the form of food or drinks that must be met for survival. The purpose of this study was to analyze the effect of population, minimum wagde, education, GRDP and growth rate on the level of food consumption in Central Java Province. The population of this study was 35 districts/cities in Central Java in 2019-2023. This study uses a quantitative approach with panel data regression analysis and uses the assistance of the Eviews10 program. The results of this study, namely the population has a negative and insignificant effect on the level of food consumption, minimum wage and growth rate have a positive and significant effect on the level of food consumption, education has a positive and insignificant effect on the level of food consumption, GRDP has a negative and significant effect on the level of food consumption. The implication of this research is that the government can adjust the minimum wage according to the growth rate and inflation to increase people's purchasing power, so that the level of food consumption can be stable or even increase.